Structural transformation and embrittlement during lithiation and delithiation cycles in an amorphous silicon electrode. (15th August 2019) - Basu, Swastik; Koratkar, Nikhil; Shi, Yunfeng
Abstract: Silicon shows potential as an anode material in lithium ion batteries due to its high specific capacity, yet its considerable volume expansion during lithiation leads to fracture and pulverization. Unfortunately, neither the atomic-level structural evolution, nor the mechanical behavior of the anode during lithiation and delithiation cycles is well understood. Interestingly, the lithiation process of a-Si provides an interesting continuum from open-structured network glass to densely-packed atomic glass, which could be used to obtain useful insights regarding commonalities in glasses. Here atomic level simulation has been used to investigate one cycle of lithiation and delithiation of amorphous silicon electrode, using Grand Canonical Monte Carlo (GCMC) and molecular dynamics (MD) simulations. The atomic level structural transformation and damage accumulation of the anode during cycling has been systematically analyzed, as well as their mechanical responses in compact tension tests. There appears to be a ductile-brittle-ductile transition for the amorphous silicon anode during both the lithiation and delithiation cycle. In other words, amorphous silicon is particularly vulnerable at intermediate lithiation. The fracture behavior of lithiated silicon was found to correlate to the Poisson's ratio, due to variations in bond covalency and structural disorder. Graphical abstract: Image 1